The Wives of Western Philosophy
1 online resource
Keywords: The Wives of Western Philosophy examines the lives and experiences of the wives and women associated with nine distinct political thinkers--from Socrates to Marx--in order to explore the gendered patterns of intellectual labor that permeate the foundations of Western political thought. Organized chronologically and representative of three eras in the history of political thought (Ancient, Early Modern, and Modern), nine critical biographical chapters explore the everyday acts of intellectual labor and partnership involving these "wives of the canon." Taking seriously their narratives as intimate partners reveals that wives have labored in remarkable ways throughout the history of political thought. In some cases, their labors mark the conceptual boundaries of political life; in others, they serve as uncredited resources for the production of political ideas. In all instances, however, these wives and intimates are pushed to the margins of the history of political thought. The Wives of Western Philosophy brings these women to the center of scholarly interest. In so doing, it provides new insights into the intellectual biographies of some of the most famed men in political theory while also raising important questions about the gendered politics of intellectual labor which shape our receptions of canonical texts and thinkers, and which sustain the academy even today.